Weed Control and Grain Sorghum (Sorghum bicolor) Tolerance to Pyrasulfotole plus Bromoxynil. (22nd November 2012) - Fromme, Dan D.; Dotray, Peter A.; Grichar, W. James; Fernandez, Carlos J.
Abstract : Field studies were conducted during the 2008 and 2009 growing seasons at five locations in the Texas grain sorghum producing regions to evaluate pyrasulfotole plus bromoxynil combinations for weed control and grain sorghum response. All pyrasulfotole plus bromoxynil combinations controlled Amaranthus palmeri, Cucumis melo, and Proboscidea louisianica at least 94% while control of Urochloa texana was never better than 69%. Pyrasulfotole plus bromoxynil combinations did result in early season chlorosis and stunting; however, by the end of the growing season no visual injury or stunting differences were noted when compared to the untreated check. Early season grain sorghum chlorosis and stunting with pyrasulfotole plus bromoxynil combinations did not affect grain sorghum yields with the exception of pyrasulfotole at 0.03 kg ai/ha plus bromoxynil at 0.26 kg ai/ha plus atrazine at 0.58 kg ai/ha applied early postemergence followed by pyrasulfotole plus bromoxynil applied mid-postemergence which reduced yield at one of two locations in 2008. Grain sorghum yield increased following all pyrasulfotole plus bromoxynil treatments compared to the untreated check in 2009.